Atomic Emission Spectra of Neutral Noble Gases in the Infrared Spectral Range. (2020) - Civiš, Svatopluk; Zanozina, Ekaterina; Pastorek, Adam; Kubelík, Petr; Ferus, Martin; Chilukoti, Ashok
No abstract available